Antagonistic and Antifungal Activities of Endophytic Fungi Isolated from Fragaria x Ananassa Against Colletotrichum Acutatum - Oktira Roka Aji; Alfiatul Laila (Universitas Teknologi Yogyakarta, Yogyakarta, Indonesia, 2025)
Fragaria x ananassa or strawberry has significant economic value worldwide. However, its cultivation faces various challenges. One example was fungal diseases, such as anthracnose, caused by Colletotrichum acutatum. Disease management generally relies heavily on synthetic fungicides, raising concerns about environmental sustainability and human health risks. Therefore, more environmentally friendly alternatives are needed, such as the use of biological agents. This study aims to assess the potential of endophytic fungi from strawberry plants as natural biocontrol agents against Colletotrichum acutatum. The study began with the isolation of endophytic fungi from strawberry tissues and their characterization morphologically. The antagonistic activity of endophytic fungi against colletotrichum acutatum was evaluated using three methods: a dual culture assay to assess direct inhibition, a cell-free filtrate assay to analyze the effect of fungal metabolites, and a volatile organic compound (VOC) assay to inhibit the growth of pathogenic pathogens. In this study, 20 fungal isolates were successfully isolated. A total of 15 showed antagonism against Colletotrichum acutatum. Isolate A1 showed potent inhibition in the dual culture test by effectively antagonizing Colletotrichum acutatum. Isolate D1 produced extracellular compounds that reduced the growth of Colletotrichum acutatum by 52.28% ± 3.21% in the cell-free filtrate assay. At the same time, isolate D3 proved most effective in the VOC assay, suppressing the growth of pathogenic colonies by 71.35% ± 3.37%. Thus, endophytic fungi, especially isolates A1, D1, and D3, have the potential to serve as an environmentally friendly alternative to combat anthracnose disease on strawberries.